Transmission Design and Force Analysis of HMCVT for High Power Tractor - He Chengkui; Lang Pengfei; Kang Min; Zhang Haijun (Jixie chuandong)
The Hydro-Mechanical Continuously Variable Transmission（ HMCVT） is a twin drive transmission,which divides the output power of the engine into mechanical power and hydraulic power through the shunting mechanism,and the power is converged by the confluence mechanism so as to realize the effect of continuously variable speed. Through consulting a large amount of documents and materials,a new transmission scheme is put forward according to the working principle of hydro mechanical stepless transmission. Based on the transmission scheme,the design and calculation of the technical parameters of the main key parts are carried out,then the final structural parameters of each component are determined,and the strength checking calculation is carried out. On this basis,the 3 D model of every part is built in Creo 2. 0,and then the virtual assembly drawing is completed. Finally,the finite element analysis of the main parts is carried out by using ANSYS. The results show that the design of this structure is reasonable.